Single-cell profiling of murine bladder cancer identifies sex-specific transcriptional signatures with prognostic relevance - Hany A. Abdel-Hafiz; Saravana Kumar Kailasam Mani; Wesley Huang; Kenneth H. Gouin, III; Yuzhou Chang; Tong Xiao; Qin Ma; Zihai Li; Simon R.V. Knott; Dan Theodorescu (iScience, 2023)
Summary: Bladder cancer (BLCA) is more common in men but more aggressive in women. Sex-based differences in cancer biology are commonly studied using a murine model with BLCA generated by N-butyl-N-(4-hydroxybutyl)-nitrosamine (BBN). While tumors in the BBN model have been profiled, these profiles provide limited information on the tumor microenvironment. Here, we applied single-cell RNA sequencing to characterize cell-type specific transcriptional differences between male and female BBN-induced tumors. We found proportional and gene expression differences in epithelial and non-epithelial subpopulations between male and female tumors. Expression of several genes predicted sex-specific survival in several human BLCA datasets. We identified novel and clinically relevant sex-specific transcriptional signatures including immune cells in the tumor microenvironment and it validated the relevance of the BBN model for studying sex differences in human BLCA. This work highlights the importance of considering sex as a biological variable in the development of new and accurate cancer markers.